Low nanomolar caffeic acid attenuates high glucose‐induced endothelial dysfunction in primary human umbilical‐vein endothelial cells by affecting NF‐κB and Nrf2 pathways. (13th July 2016) - Fratantonio, Deborah; Speciale, Antonio; Canali, Raffaella; Natarelli, Lucia; Ferrari, Daniela; Saija, Antonina; Virgili, Fabio; Cimino, Francesco
Abstract: Hyperglycemia contributes to dysregulate endothelial function associated with diabetes, leading to initiation and propagation of vascular complications and dysfunction. Caffeic acid (CA), a dietary hydroxycinnamic acid abundant in coffee, has been reported to exert antidiabetic effects in rat models. Herein, we investigated the molecular effects of physiological concentrations of CA (10 nM) against endothelial dysfunction induced by high glucose (HG) in human endothelial cells (HUVECs). HUVECs were exposed to HG 25 mM, to mimic diabetic condition, in presence of CA. Intracellular redox status (reduced glutathione, superoxide dismutase (SOD) and total antioxidant activity levels), and NF‐κB pathway were examined. We also evaluated the involvement of NF‐E2‐related factor 2 (Nrf2)/electrophile responsive element (EpRE) pathway. Our data show that CA inhibits HG‐induced nuclear translocation of NF‐κB and the downstream expression of endothelial adhesion molecule 1 and restores antioxidant levels by upregulating Nrf2/EpRE pathway. Our data suggest that CA can suppress several aspects of HG‐induced endothelial dysfunction through the modulation of intracellular redox status controlled by the transcription factor Nrf2. These findings highlight that low physiological concentration of CA achievable specifically upon food consumption are able to prevent endothelial dysfunction associated with inflammation and oxidative stress induced by high concentration of glucose. © 2016 BioFactors, 43(1):54–62, 2017